Relay race in the coeducational maze - de Ignacio, Sacha (Filanderas, 2019)
The article focuses on the question: why does education resist equality? Eulàlia Lledó kicked off Filanderas with «Language, literature and coeducation», where she unraveled the details of time, effort and love that teachers, mostly women, dedicate to the inclusion of equality in educational life «usually in an invisible or invisible way by administrations» (2016: 74). From the progressive implementation of gender policies, creation of national and regional laws regulating the incorporation of equality in the education system, regulations, pacts (including the recent approval of the State Pact on Sexist Violence), the inclusion of educational equality continues to be hampered by the idiosyncrasy of the educational system itself and the policies that govern it. This article is based on the analysis of this situation, as well as on the evaluation of the consequences of the absence of generalized equality in the education system.